The impact of online games on creativity and the role of imagination - Yung-hsun Cheng (Frontiers in Behavioral Neuroscience)
Background studyThe rapid growth of online gaming has sparked interest in its potential effects on cognitive abilities such as creativity. Previous research indicates that interactive digital environments may enhance creative skills through immersive gameplay. However, the role of imagination as a mediator in the relationship between gaming and creativity remains under-explored. This study investigates how playing online games influences creativity and examines the mediating effect of imagination in this relationship.ObjectivesThe primary objectives of this research are to: (1) evaluate the direct impact of online gaming: investigate how participation in online gaming affects players’ imagination and creativity levels, measuring specific outcomes through qualitative and quantitative assessments. (2) explore the mediating role of imagination: analyze the relationship between players’ motivation for gaming and their creative output, focusing on how imagination serves as a mediating factor in this dynamic. (3) differentiate game types and their effects: assess how various genres of online games, specifically role-playing games (RPGs) and sandbox games, uniquely influence players’ imaginative capabilities and creative expressions, using comparative analyses to highlight differences in outcomes.MethodsThis study employed a mixed-method approach, combining survey questionnaires and experimental procedures. The survey collected responses from 202 participants, gathering insights into their gaming behaviors, motivations, and perceived creativity. For the experimental segment, 12 participants (6 males, 6 females) were divided equally into experimental and control groups. Participants were assigned to either play Genshin Impact (a RPG) or Roblox (a sandbox game) to observe differences in creativity and imagination lasting for four weeks. Data were analyzed to determine the relationship between gaming motivation, imagination, and creativity. However, the goal of this work was to investigate whether exclusive play of either Roblox or Genshin Impact over a four-week period would differentially influence player motivation, creativity, and imagination.ResultsResults from the survey and experimental data indicate a significant relationship between players’ motivation and post-game imagination. Notably, gaming motivation also had a significant impact on creativity, particularly in Genshin Impact and Roblox. The findings confirmed that imagination acts as a mediator between motivation and creativity, suggesting that players who are more motivated display enhanced creative abilities, partly due to increased imaginative engagement during gameplay.ConclusionThe study concludes that online gaming can positively influence creativity, especially when imagination mediates the relationship between gaming motivation and creative outcomes. These results underscore the potential cognitive benefits of online games, particularly for players with high levels of motivation, and highlight the distinct roles of RPGs and sandbox games in fostering creativity.